Enhanced Stability of Gold Nanoparticles with Thioalkylated Carboxyl-Terminated Ligands for Applications in Biosensing - Sawinee Ngernpimai; Theerapong Puangmali; Atcha Kopwitthaya; Patcharaporn Tippayawat; Apiwat Chompoosor; Saowapak Teerasong (ACS Applied Nano Materials, 2024)
Gold nanoparticles (AuNPs) are widely recognized for their remarkable optical and chemical properties, making them versatile materials with diverse applications in sensing, catalysis, and biomedical fields. However, their susceptibility to aggregation and poor dispersion under different environmental stresses limits their utility in practical applications. In this study, we investigate the efficacy of utilizing carboxylate-terminated ligands to stabilize AuNPs and enhance their stability and functionality. Through a series of experiments, including assessments of pH buffer effects, ionic strength variations, freeze-drying stress, and protein adsorption, we demonstrate the effectiveness of these ligands in maintaining the stability of AuNPs within a pH range of 5–10. This enables them to resist aggregation in the presence of high concentrations of electrolytes and facilitates rapid redispersion after freeze-drying, enabling long-term storage of AuNPs in a dry powder form without compromising their stability or functionality. Moreover, the ligands efficiently prevent nonspecific protein binding. We explore application of these stabilized AuNPs conjugated with specific monoclonal antibodies for detection of Listeria monocytogenes, highlighting their potential for use in biosensing applications. This research underscores the significance of carboxylate-terminated ligands in stabilizing AuNPs, offering insights into the development of reliable and functional nanomaterials for various biomedical and biosensing applications.
Keywords: Gold and Silver Nanoparticles Synthesis and Applications; Nanocluster Synthesis and Applications; Nanomaterials for catalytic reactions